If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -5 = 1 + 6x Reorder the terms: -5 + 9x = 1 + 6x Solving -5 + 9x = 1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -5 + 9x + -6x = 1 + 6x + -6x Combine like terms: 9x + -6x = 3x -5 + 3x = 1 + 6x + -6x Combine like terms: 6x + -6x = 0 -5 + 3x = 1 + 0 -5 + 3x = 1 Add '5' to each side of the equation. -5 + 5 + 3x = 1 + 5 Combine like terms: -5 + 5 = 0 0 + 3x = 1 + 5 3x = 1 + 5 Combine like terms: 1 + 5 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| 6m=-6+144 | | [21+(-21)]+[21+(-25)]= | | 10m-29=71whatsm | | 3w+8x-13y+6w+7x+8y= | | 10y=2x-13 | | ln(e^4*x)+8=0 | | 14x+40=360 | | -8+10-(-7)-20+19= | | X^2+x-1=5x | | ln(e^4x)+8=0 | | 2X+3Y+8+2X+4+1Y=360 | | t=25-0.25n | | 0.20+1x=0.25 | | -9(10)= | | 6f+2f+f=180 | | 4(x-10)=-6(2-2x)-6 | | 0=3n^2-10n+4 | | 4x-71=94-7x | | x-(-2)=(-7) | | 7y+5x=14 | | 3a-(5a-4)=-4 | | -9x-49=39-5x | | 6x+20y=30 | | 20x+13g-13x= | | -6x-35=-8x+11 | | x-2=(-7) | | 5x-40=11+2x | | -122+6x=-5x+53 | | X+.15x= | | -6-35=-8+11 | | -51+5x=-7x+105 | | 13b=b+37 |